The Legitimacy of the Taliban Government after the 2021 Takeover: An International Law Perspective - Anila A (Program Magister Ilmu Hukum Universitas Ekasakti, 2026)
This study examines the legitimacy of the Taliban government following its takeover of power in Afghanistan from the perspective of international law. The issue arises due to the discrepancy between de facto territorial control and acceptance within the international system. This study aims to analyze the legitimacy of the Taliban government based on the concepts of effective control, the origin of power, the exercise of power, and international recognition. The research method used is normative legal research employing a conceptual approach and a case-based approach through a literature review. The results indicate that the Taliban have met the element of effective control by controlling territory and actually performing governmental functions. However, the process of the power takeover and government policies that impact human rights influence the level of international acceptance. Furthermore, most countries have not yet granted official recognition to the Taliban government, although there are limited cooperative relations. This study concludes that the legitimacy of the Taliban government is in an ambiguous position: on one hand, it functions as a de facto governing authority, and on the other hand, it has not yet gained widespread recognition within the international legal system.